1999
DOI: 10.1063/1.124576
|View full text |Cite
|
Sign up to set email alerts
|

Growth of epitaxial silicon at low temperatures using hot-wire chemical vapor deposition

Abstract: We demonstrate epitaxial silicon growth of 8 Å/s at temperatures as low as 195 °C, using hot-wire chemical vapor deposition. Characterization by transmission electron microscopy shows epitaxial layers of Si. We briefly discuss various aspects of the process parameter space. Finally, we consider differences in the chemical kinetics of this process when compared to other epitaxial deposition techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 18 publications
0
19
1
2
Order By: Relevance
“…Under many conditions, HWCVD results in low-temperature epitaxy of silicon on c-Si substrates [4] at temperatures as low as 195 -C. In high-efficiency heterojunction solar cells, a thin (¨5 nm) intrinsic a-Si:H layer must be interposed between the base wafer and the heavily doped a-Si:H emitter [5], because intrinsic a-Si:H has a far lower density of defects than a doped a-Si:H layer [6]. A lower density of mid-gap trap states reduces the trap-assisted inter-band tunneling-recombination rate across the a-Si/c-Si interface, thereby suppressing deleterious saturation current.…”
Section: Introductionmentioning
confidence: 99%
“…Under many conditions, HWCVD results in low-temperature epitaxy of silicon on c-Si substrates [4] at temperatures as low as 195 -C. In high-efficiency heterojunction solar cells, a thin (¨5 nm) intrinsic a-Si:H layer must be interposed between the base wafer and the heavily doped a-Si:H emitter [5], because intrinsic a-Si:H has a far lower density of defects than a doped a-Si:H layer [6]. A lower density of mid-gap trap states reduces the trap-assisted inter-band tunneling-recombination rate across the a-Si/c-Si interface, thereby suppressing deleterious saturation current.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The process of growing epitaxial thin film by MBE is quite involved and complicated, and therefore the efforts/scope for finding simpler deposition techniques remains alive. Tanaka et al 5 have reported growth of very high quality epitaxial Si from silane on Si-wafer by hot-wire ͑HW͒ chemical vapor deposition ͑CVD͒ at T s ϭ350°C and almost simultaneously Thiesen et al 6 reported similar epitaxial growth. However, at a lower T s (195°C) Thiesen et al 6 could grow only 30 nm epitaxial Si film.…”
mentioning
confidence: 71%
“…Для ускорения процесса пиролиза газов в реакторе установки в настоящее время предложены и используются разно-образные методы. Наиболее распространенными из них являются повышение давления рабочих газов в реак-торе, т. е. переход к технологиям проточного типа при пониженном давлении [2], либо использование метода " горячей проволоки" [7]. Суть последнего состоит в помещении перед подложкой разогретого до высокой температуры элемента, например вольфрамовой прово-локи, выступающей в качестве источника формирования в методе химической эпитаксии дополнительных атомар-ных потоков [8].…”
Section: (поступило в редакцию 14 июня 2016 г)unclassified